Novel Chlorin with a HYNIC: Synthesis, 99mTc-Radiolabeling, and Initial Preclinical Evaluation; Molecules; Vol. 30, iss. 1 - Popov A. Alexander; Suvorov N. Nikita; Larkina M. S. Mariya Sergeevna; Plotnikov E. V. Evgeny Vladimirovich; Varvashenya R. N. Ruslan Nikolaevich; Bodenko V. V. Vitalina Vasiljevna; Yanovich G. Gleb; Ostroverkhov P. Petr; Usachev M. Maxim; Filonenko E. Elena; Belousov M. V. Mikhail Valerjevich; Grin M. Mikhail (2025, 2025)
Title screen